Hemodynamic changes and their relationship with white matter hyperintensities in CSVD patients with cognitive impairment: a 4D flow study - Cao, Jiajun; Yuan, Chang; Zhang, Zhenpeng; Zhao, Xiaoying; Zhang, Yukun; Chang, Peipei; Song, Qingwei; Zhang, Bingwei; Hu, Rui; Miao, Yanwei (Frontiers in Aging Neuroscience, 2025)
ObjectiveTo observe the hemodynamics of intracranial arteries and veins in patients with cerebral small vessel disease (CSVD) with cognitive impairment (CI), and to explore the association between these flow features and white matter hyperintensities (WMH).Materials and methodsA total of 53 patients with CSVD were included in the study, comprising 30 patients with CI (CI group) and 23 patients with non-CI (NCI group); Meanwhile, 25 age-matched cognitively healthy volunteers were recruited. WMH burden was evaluated using a 2D axial T2-FLAIR sequence. A 4D flow MRI was employed to measure intracranial hemodynamic features, including cross-sectional area, flow rate, blood flow velocity, wall shear stress (WSS), pulsatility index, and resistive index in the internal carotid artery (ICA), middle cerebral artery, basilar artery (BA), transverse sinus (TS), straight sinus (SS), and superior sagittal sinus (SSS). CSF-Q flow, a 2D PC MRI sequence, was performed to calculate the CSF fluid dynamics in the midbrain aqueduct.ResultsThe CSVD with CI population reported a statistically significant decrease in flow rate, blood flow velocity, and WSS, as well as an increase in PI, RI, CSF flow quantity, and velocity compared to age-matched cognitively healthy control participants. There was a moderately positive correlation between MMSE, MoCA score and flow rate, flow velocity, and WSS (r = 0.226–0.544, all P < 0.05), and a moderately negative correlation between MMSE, MoCA score and PI, RI (r = −0.230 to −0.406, all P < 0.05). Multiple linear regression indicated that, the flow rate and mean velocity in venous sinuses (β = −0.472 to −0.381, all P < 0.05) and the WSS in arterial segments (β = −0.771 to −0.441, all P < 0.05) had independently negative association with WMH burden; Meanwhile, a significant positive relationship was found between PI in arterial segments and specific-distributed WMH (PVWMH and S-CC WMH) (β = 0.239 to 0.356, all P < 0.05).ConclusionThe intracranial hemodynamics were associated with CI and WMH in patients with CSVD. 4D flow MRI can be used as a non-invasive method to assess cerebrovascular hemodynamics and helps to identify patients who may benefit from interventions to improve the functions of the cerebral circulatory system and provides a potential new path for clinical treatment.